2020
DOI: 10.1016/j.ebiom.2019.11.035
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic and druggable hPG80 (Progastrin) is overexpressed in multiple cancers and detected in the blood of patients

Abstract: Background: In colorectal cancer, hPG80 (progastrin) is released from tumor cells, promotes cancer stem cells (CSC) self-renewal and is detected in the blood of patients. Because the gene GAST that encodes hPG80 is a target gene of oncogenic pathways that are activated in many tumor types, we hypothesized that hPG80 could be expressed by tumors from various origins other than colorectal cancers, be a drug target and be detectable in the blood of these patients. Methods: hPG80 expression was monitored by fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…The close relationship between hPG80 and cancer progression has been previously reported in several studies [21,[24][25][26][27][28]. We have recently shown that tumor cells from many cell types overexpress hPG80 [17]. Its expression is related to cancer cell activity and represents a risk factor for tumor recurrence and therefore hPG80 may provide prognostic significance in metastatic stages of tumors which secrete hPG80 in measurable amounts.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The close relationship between hPG80 and cancer progression has been previously reported in several studies [21,[24][25][26][27][28]. We have recently shown that tumor cells from many cell types overexpress hPG80 [17]. Its expression is related to cancer cell activity and represents a risk factor for tumor recurrence and therefore hPG80 may provide prognostic significance in metastatic stages of tumors which secrete hPG80 in measurable amounts.…”
Section: Discussionsupporting
confidence: 65%
“…We have reported previously [17] progastrin to be elevated in plasma of patients with metastatic kidney cancer. In physiology, progastrin is the precursor of gastrin synthetized by antrum G cells and processed into gastrin [18].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The analytical sensitivity obtained for the DxPG 80 is a LoD of 1 pM and a LLoQ of 3.3 pM. Of note, the calculation is slightly different from the LoD and LLoQ described in 24,25 to follow the exact guideline EMEA/CHMP/EWP/192217/2009.…”
Section: (B) Measuring Range Of Assaymentioning
confidence: 82%
“…The presence of hPG 80 in the blood reects the variations in the tumor: (1) plasma levels correlate with mRNA expression (lung cancer; Spearman r ¼ 0.8; p ¼ 0.0023); (2) plasma levels signicantly decrease upon surgery (peritoneal carcinomatosis decrease from 5.36 pM (before surgery) to 3.00 pM (post surgery), p <0.0001 and upon remission (hepatocellular cancer, decrease from 11.54 pM to 1.99 pM (p < 0.0001); (3) the level of hPG 80 at diagnostic is a prognostic factor in metastatic renal cell carcinoma (mRCC) patients: Furthermore, mRCC patients with high hPG 80 levels (>4.5 pM) had signicantly lower OS (overall survival) compared to patients with low hPG 80 levels (<4.5 pM) (12 versus 31.2 months, respectively; p ¼ 0.0031); (4) efficacy of treatments correlates with hPG 80 level kinetic variations and recurrence is associated with an increase in hPG 80 level (hepatocellular cancer). 25 All these data re-inforce the value of hPG 80 as a new cancer target and prone to the usefulness of the detection of hPG 80 in the blood.…”
Section: Discussionmentioning
confidence: 94%